WHOLE BLOOD GLUCOSE: BIOMARKER OF COMMON ON-FARM PROCEDURES IN JUVENILE Clarias gariepinus - GABRIEL, U.U; AKINROTIMI, O.A. (Nigerian Journal of Fisheries, 2011)
Juveniles of Clarias gariepinus (mean weight, 180.56  15.76 g; mean total length, 13.57  3.78 cm SD) were exposed to five on-farm procedures (exposure outside water, sorting, starvation, serial transfer and overcrowding) and whole blood was collected before each treatment and at 20, 40 and 60 mins. After fish were exposed to each procedure, blood glucose levels were determined using a glucose meter. In all the procedures the glucose level increased with duration (p  0.05) with a peak at 60 minutes. Whole blood glucose was highest in fish exposed outside water in comparison to the other treatments (p  0.05). This study revealed that common onfarm procedures such as the ones studied can cause stress in C. gariepinus as evident in a raised glucose level. Hence this should be minimized as much as possible to reduce the effect of these procedures on the fish.